Do Turbans Provide Protection Against Cranial Trauma in Two-Wheeler Accidents? A Review of the Indian Medical Literature - Dirk HR Spennemann (Institute of Medico-legal Publications Pvt Ltd, 2020)
The wearing of turbans or head scarves is mandatory for practising Sikh men and women. Religious mandatesstipulate that nothing may be placed on top of the turban (scarf), thus making it impossible for practicing Sikhs towear protective motorcycle helmets. To honour the freedom of religious expression, many jurisdictions, includingIndia, have exempted Sikhs from mandatory helmet laws. Despite studies into the efficacy of protective helmetswhile riding ‘two-wheelers,’ little is known about the protective potential of turbans. This paper represents a reviewof Indian literature (277 studies) related to head injuries sustained in road traffic accidents involving two-wheelers.This review shows that the extant literature is of limited value when trying to understand the extent of the protectivepotential of turbans and that systematic, evidence-based epidemiological studies derived from hospital admissionsand forensic examinations are required.